Synchronous online learning and career readiness in higher education: student perceptions, challenges, and solutions - Lukashe, Mihlali; Chigbu, Bianca Ifeoma; Umejesi, Ikechukwu (Frontiers in Education, 2024)
Synchronous Online Learning (SOL) environments have transformed the educational landscape; however, their efficacy in equipping students with the necessary skills to succeed in the workforce is still significantly understudied. This research examines the influence of SOL on students' career readiness, with a particular emphasis on developing essential professional skills such as digital literacy, interpersonal communication, and practical experience. To ascertain the perceptions and experiences of 27 third-and fourth-year students, data were acquired through in-depth interviews and analyzed thematically using a qualitative research methodology. The research indicates that SOL effectively enhances technical skills and digital adaptability; however, it is substantially inadequate in nurturing interpersonal skills and offering practical, hands-on experiences. Students noted a decrease in networking opportunities and expressed apprehension regarding their lack of preparation for the demands of real-world employment. The research underlines the importance of educational innovations that assist in integrating the advantages of digital learning with the development of comprehensive professional competencies.